WAYS OF TRAINING AND PROFESSIONAL TEACHING IN BRAZIL: CHALLENGES AND PROSPECTS IN COMTEMPORARY - Patrícia Rodrigues Kimura; Rita Cassia Cabral; Ivany Pinto do Nascimento; Wilma Baía Coelho (Editora da Universidade de Santa Cruz do Sul, 2012)
This article has the object of study, training and professionalization of Teachers in Brazil. Its objective is to outline a brief overview about the Teacher, pointing to its close relationship with the issue of teachers professionalization, Seeking to relate the overlap of these two dimensions in the educational process, marking the main demands of the teachers and the current issues that still require the status of the profession. With the theoretical and methodological literature review with the authors Veiga (2005); RAMALHO, NUÑEZ e GAUTHIER, (2004) e Nóvoa (1997) that demonstrate a context of restructuring of teachers' work.